Some Diagnostic and Anatomical Characteristics of Five Taxa from Boraginaceae Juss. Family Erbil, Sulemania and Duhok -Iraq. - Narmin A. Saeed; Jawhar F. Saeed (Zanco Journal of Pure and Applied Sciences, 2021)
Some anatomical characteristics of five taxa belong to Boraginaceae family (Asperugo procumbens L._Boiss, Buglossoides arvensis L._Boiss, B. tenuiflorum L. (fil)_Boiss, B. incrassatum Guss_Boiss and Symphytum kurdicum Boiss.et Haussk). The study was performed in the mountain region at the north of Iraq were examined the field trips have done at the growth period during the year 2019. Some parts of specimens were anatomically examined by paraffin method, the diagnostic characters of stems, leaves and leaf petioles were identified. Glandular and non-glandular hairs of each species have been determined, the different trichomes in adaxial and abaxial of both leaf surfaces and stems were present. The shapes of stem in cross sections were different between the species, lysigenous canals were present in the stem of B. tenuiflorum and S. kurdicum and the drusses were present only in stem of B. incrassatum. The main vascular bundle found in the midrib, the leaf margin shapes were different between species.